Ink‐jet printing of cotton with natural dyes. (14th April 2014) - Savvidis, George; Karanikas, Evangelos; Nikolaidis, Nikolaos; Eleftheriadis, Ioannis; Tsatsaroni, Eforia
<x xml:space="preserve">Abstract</x> Four natural dyes, annatto, cutch, pomegranate fruit rind, and golden dock, were used as colorants for the preparation of water‐based ink‐jet inks for digital textile printing. The physical and rheological properties (pH, conductivity, surface tension, and viscosity) of the inks were measured over a period of 90 days for the evaluation of ink stability and suitability for ink‐jet printing. The inks were found to be suitable and were used for the digital printing of cotton fabrics. The prints were subjected to wash, light, and rub fastness tests and colour measurements. Colour consistency and fastness results, especially after fixation, are comparable with those of synthetic dyes, which paves the way for the production of environmentally friendly ink‐jet inks using natural dyes for the digital printing of cotton through the formulation of suitable printing techniques.